Examining the Relationships between Career Development, Daily Life Decision Making and Social Emotional Learning Skills of Middle School Students - BULUT, Beyza; BACANLI, Feride (Journal of Ecohumanism, 2024)
This presented research has three purposes: The first purpose of this study is to examine the power of middle school students' social emotional learning and daily life decision-making skills together as a predictor of their career development. The second purpose is to examine the career development of middle school students according to gender. Third purpose is to examine the career development of middle school students according to targeted high school type. The research group consisted of 263 middle school students (141 female, 116 male, 6 unknown). These students were studying in 3 middle schools in the center of a large city in the northwestern part of Turkey and their ages ranged between 10-15 (X̄=12.31; sd=1.07). The research data were collected by applying the Chilhood Career Development Scale, Social Emotional Learning Scale for Adolescents, Daily Life Decision Making Scale and Personal Information Form. The research data were analysed using multiple linear regression analysis, t test, and one-way ANOVA. The research results showed that middle school students' social emotional learning and daily life decision-making skills scores together accounted for a significant proportion of the variance 0.19% of the career development scores of middle school students. The results showed that the career development score mean of students targeted Anatolian high school were higher than those aiming for science high school and vocational and technical high school. There was not significantly differences in career development scores of the students according to gender. The research results were discussed based on the relevant literature, provided important implications for the theoretical and practical literature on career development, social emotional learning and daily life decision-making skills and suggestions were presented for future theoretical and practical research.